ANALISIS KINERJA APARATUR DESA DALAM MEMBERIKAN PELAYANAN PUBLIK: STUDI KASUS DI DESA KARANGGEGER KECAMATAN PAJARAKAN KABUPATEN PROBOBOLINGGO - Eko Wicaksono; Samsul Maulana Ilyas (Jurnal Bina Bangsa Ekonomika, 2022)
The quantity and quality of work done by employees requires a concern and compassion from the employees concerned in order to develop skills and expertise in supporting the success of a particular organization or agency. There is a synergistic performance improvement effort that each employee is required to optimize all the talent that can be found in employees in an effort to develop the capacity in serving the community, both individually and the team of all elements of work must be implemented proportionally so that what is desired can be realized at the cost and time available. This study uses descriptive research with qualitative analysis which focuses on efforts to explain the description (picture) related to the administrative skills of village officials in public services in Karanggeger Village with a view to knowing the performance of karanggeger village apparatus in providing public services. The results of this study show that the technical capabilities of karanggeger village administrative apparatus have not been able to be relatively good. This is because the majority of village officials in Karanggeger Village only pursue the most high school education, not least the head of his own. Village officials in the ability to be humane are not cut down, all get the same treatment and tend to attach importance to the needs of the community everything is done appropriately regardless of social status. In the implementation of administrative duties the ability of karanggeger village apparatus is quite low. It can be proven in the field, there are still complaints from people who perform services in Karanggeger Village